Talent (cai) as an object of philosophical and anthropological investigation in traditional China - Poškaitė, Loreta (Acta Orientalia Vilnensia, 2007)
This article deals with the treatment of human talent (cai 才) in pre-imperial and early imperial China and concentrates on its relationship with other Chinese philosophical and anthropological concepts and the general cultural context. On the one hand, it analyses the moral meaning of talent, discussing its relationship with the concept of xian 贤 ( the worthy) in Classical Confucianism, and on the other hand it analyses its relationship with the concept of de 德 (virtue) as it was treated from Classical Confucianism and Legalism to the Six Dynasties. The latter analysis is based mainly on books by Xu Gan Zhong lun 中论 (Balanced Discources) and Liu Shao Renwuzhi 人物志 (The Study of Human Abilities), paying special attention to the infiltration of the Legalist understanding of cai into those books. The second problem discussed here is the relationship of cai and human nature (xing). The author argues that the discussions concerning human resources or talent in pre-imperial and early imperial China were inseparable from the anthropological and philosophical thinking on human nature and from the resolution of political problems. The understanding of human resources in China had from the very beginning a strong motivation for applicability in the political sphere, and this was a contribution not only of Confucian thinkers, but also by the schools of Legalists, Logicians (or School of Names), and Dialecticians (or School of Yin-yang). This could be the reason why the Chinese avoided the mystification, essentialisation and romanticisation of human talent, as happened in Western culture (especially with the titanism of the Renaissance and beyond).
Keywords: -